Nanoscale mapping of newly-synthesised phospholipid molecules in a biological cell using tip-enhanced Raman spectroscopy. Issue 16 (8th February 2017) - Kumar, Naresh; Drozdz, Marek M.; Jiang, Haibo; Santos, Daniela M.; Vaux, David J.
Abstract : Non-destructive & label-free nanoscale mapping of newly-synthesised phospholipid molecules inside a biological cell is demonstrated using tip-enhanced Raman spectroscopy for the first time. Abstract : Nanoscale chemical mapping of newly-synthesised phospholipid molecules inside a mammalian cell is demonstrated using tip-enhanced Raman spectroscopy (TERS) for the first time using mouse pre-adipocyte cells as a model system. Newly-synthesised membrane phospholipid distribution within a pre-adipocyte cell is mapped with <20 nm spatial resolution, overcoming the diffraction limit of confocal Raman spectroscopy via plasmonic enhancement of Raman signals at a TERS tip-apex.